Detection of KPC carbapenem-hydrolyzing enzymes in Enterobacter spp. from Brooklyn, New York - Bratu, Simona (Animo Repository, 2005)
Enterobacter spp. are rarely resistant to carbapenems. In this report, one Enterobacter sp. isolate possessed bla KPC-3 and two possessed bla KPC-2. For all three strains, the imipenem MICs were dependent on the inoculum and testing method; two were reported by the clinical laboratories to be carbapenem susceptible. Improved detection methods will be necessary to identify these enzymes.